KOLONISASI MIKROBIOTA NORMAL DAN PENGARUHNYA PADA PERKEMBANGAN SISTEM IMUNITAS NEONATAL - kusumo, pratiwi (MAJALAH ILMIAH WIDYA, 2012)
Early microbiota colonization of the neonates (infant) gastrointestinal tract is crucial for the overall health of the infant, andestablishment and maintenance of non-pathogenic intestinal microbiota may reduce several neonatal inflammatory conditions. Balancingto the gastrointestinal microbiota colonization between comensal (non pathogenic) and pathogenic microbiota influence the developmentof immune system neonates. There several factor thatâs influence the development of immune system in gastrointestinal neonates.These factor is 1).Administration of antibiotic, 2).Diet of probiotic,prebiotic and symbiotic 3). Mode of delivery 4). Suplementation ofbreast milk. All these factor maintance the colonization process in gastrointestinal according to exposure pathogen in early life ofneonates